Evaluate each expression using the graphs of y=f(x) and y = g(x) shown below.(a) (gof)(-1) (b) (gof)(0) (c) (fog) - 1) (d) (fog)(4)
![Evaluate each expression using the graphs of yfx and y gx shown belowa gof1 b gof0 c fog 1 d fog4 class=](https://us-static.z-dn.net/files/d1a/9e11d171dce05aa76af75e1c105ed695.png)
![Evaluate each expression using the graphs of yfx and y gx shown belowa gof1 b gof0 c fog 1 d fog4 class=](https://us-static.z-dn.net/files/db4/6c4b5302f408c4a09186e964f5e830c1.png)
Answer:
a) 5
b) 6
c) -2
d) -3
Explanation:
Given:
a) From the graph, we can see that f(-1) = 1 and g(1) = 5, so we'll have that;
[tex](g\circ f)(-1)=g(f(-1))=g(1)=5[/tex]b) From the graph, we can notice that f(0) = 0, g(0) = 6, so we'll have that;
[tex](g\circ f)(0)=g(f(0))=g(0)=6[/tex]c) From the graph, we can notice that g(-1) = 4 and f(4) = -2, so we'll have that;
[tex](f\circ g)(-1)=f(g(-1))=f(4)=-2[/tex]d) From the graph, we can see that g(4) = 3 and f(3) = -3, so we'll have that;
[tex](f\circ g)(4)=f(g(4))=f(4)=-3[/tex]